Potassium in young children - Mann, M D (Department of Paediatrics and Child Health, 2020)
Potassium i.s one of the major constituents of the human body but its role in metabolism is not clearly defined. One reason for this is the predominant intracellular distribution of the ion and the attendant difficulties in the detection of deficiency states. Serum potassium levels are of little value as over 95% of the potassium in the body is intracellular. Balance studies and the analysis of biopsy material have been used. However, they are so time consuming that they are only of use in establishing the diagnosis retrospectively and give very little indication of the severity of the deficit. Exchangeable potassium measurements do give an indication of the severity of the deficit. However, they involve the administration of an isotope which is not always available because of its short half-life. The development of the whole body counter has overcome most of these problems.